A comparative study of entrepreneurship education and entrepreneurial intentions amongst students at selected South African institutions of higher education - Matsheke, Moses Jametane (Vaal University of Technology, 2022)
Entrepreneurial intention (EI) is considered as an element used by researchers to measure the propensity of individuals to become entrepreneurs. Higher education institutions (HEIs) have been utilised globally by governments as mechanisms to increase the EIs of students by establishing entrepreneurship as an academic discipline and instituting entrepreneurship programmes at all educational levels. However, in South Africa, the Global Entrepreneurship Monitor (GEM) reports a decline in EIs in the last decade of the population aged 18-64 years. The current study investigated the influence of the entrepreneurship education (EE) at one selected Technical and Vocational Education and Training (TVET) college and a University of Technology (UOT) located in the Gauteng Province, South Africa through a comparative analysis. The Theory of Planned Behaviour (TPB) and the Theory of Reasoned Action (TRA) were used as theories to underpin the study. In addition, Self-efficacy (SE), Need to Achieve (NA) and Instrumental Readiness (IR) were included as constructs to examine further variables for EIs. The study adopted a survey design and followed a quantitative research approach in determining the relationship between the identified variables. A self-administered survey questionnaire was used to gather the data from the sampled students at the selected HEIs. The total number of usable questionnaires was 390 from the TVET college and 362 from the UOT, giving a total of 752 responses. The empirical analysis was performed by means of the descriptive statistics, exploratory factor analysis (EFA), Pearson correlations, and regression analysis. The descriptive analysis procedure was utilised to examine the demographic profile of the respondents as well as the perceptions of the respondents towards the research constructs of the study. The EFA procedure confirmed that all measurement scales applied in the study were unidimensional. The Pearson correlation analysis was used to examine the linear association between the constructs while the regression analysis was used to test the hypotheses. The results of the hypotheses tests revealed that EE was statistically significant in predicting the EI of the students from both the TVET college and UOT. The tests further revealed that EE was also statistically significant in predicting the Attitude towards Behaviour (ATB), Subjective Norm (SN), Perceived Behavioural Control (PBC), SE, NA and IR of the students from both HEIs in a similar manner. However, PBC, SE, and NA were found to be statistically insignificant for the TVET college students while for the UOT students only SN, NA and IR were statistically insignificant. The study concludes that EE is an important tool that can be used to enhance the EI of the students at both types of HEIs. It further draws the conclusion that students from the TVET college are more dependent on external factors such as the support of their families and friends as well as the availability of resources to start thinking of starting their own business, whereas those from the UOT are more reliant on internal motivation. Based on the results, the study recommends that subjects in the curriculum in HEIs should have a learning unit dedicated to stimulating entrepreneurship amongst students. Such an approach might inspire students to venture into entrepreneurship.
Ph. D. (Department of Business Administration, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Entrepreneurial intention (EI); Entrepreneurship education; Higher Education Institutions (HEIs); Global entrepreneurship monitor (GEM); Technical and Vocational Education and Training (TVET); Dissertations, Academic -- South Africa.; Entrepreneurship -- Study and teaching (Higher).; Education, Higher -- South Africa.